Ileocolic to Right Iliac Arterial Transposition for the Treatment of Chronic Mesenteric Ischemia - Al-Jundi, Wissam; Haqzad, Yama; Madbak, Khalil; Chan, Phillip (International Journal of Angiology, 2013)
The treatment of chronic mesenteric ischemia remains challenging and controversy exists over the best interventional option. Endovascular treatment has emerged as first-line management due to its associated lower morbidity and mortality than surgical reconstruction. However, open mesenteric reconstructions continue to play an important role in patients with lesions that are unsuitable for an endovascular option. Mesenteric operations utilize the aorta or iliac artery as the inflow source for a vein or prosthetic bypass to the celiac artery or superior mesenteric artery. We describe an exceptional case of chronic mesenteric ischemia due to atherosclerosis that was treated successfully with a novel ileocolic to right iliac arterial transposition.
Keywords: mesenteric ischemia; endovascular; arterial bypass; arterial transposition